Oral mucosa and therapy of recurrent aphthous stomatitis - Landová, Hana; Daněk, Zdeněk; Gajdziok, Jan; Vetchý, David; Stembírek, Jan (Ceska a Slovenska farmacie, 2013)
UNLABELLED: Oral mucosa is one of the specific surfaces of the human body, which is permanently exposed to external factors related with food intake, breathing and speaking processes, which can lead to the onset of some problems. Disorders of the oral mucosa are a group of diseases, affecting, in the course of life, the majority of the population. Many of the oral mucosa ailments are manifested by lesions. Recurrent aphthous stomatitis (RAS) is the most common of these diseases. Despite much clinical and research attention, its causes remain poorly understood and treatment is only symptomatic. RAS is reported to affect up to 25% of the population worldwide. Topical or systemic therapy (corticosteroids, antiseptics, anti-inflamatory drugs, immunomodulating agents, etc.) can be used for treatment of RAS-associated symptoms. In general, topical therapy should be preferred due to the smaller drug load of the organism. In both cases, the active substance has to be in suitable dosage form. Recently, besides the conventional ways of application (rinses), the main disadvantage of which is the short time of resistance in the oral cavity, mucoadhesive dosage forms are used. The aim of this article is to give a theoretical overview of the oral mucosa topic and its most frequent disease - recurrent aphthous stomatitis in terms of various types of the disease classification, diagnosis and therapy, and in terms of the usage of various types of active substances and medical forms. KEYWORDS: oral mucosa recurrent aphthous stomatitis therapy mucoadhesive dosage forms.
Keywords: Anti-Infective Agents, Local; ústní sliznice; aftózní stomatitida; Mouth Mucosa; Stomatitis, Aphthous; Humans; antiinfekční látky lokální; lidé